Processing, microstructure, properties and performance of thermal sprayed ceramic coatings from powder, suspension and solution precursor - Tejero Martin, Daniel (2022)
Ceramic coatings are applied in many sectors, ranging from functional coatings to high temperature coatings for aerospace engines. Typically, the deposition technique chosen represents a compromise between the required properties and the economic restrains. Over the years, thermal spraying has proven itself as a reliable and cost-efficient method for the deposition of a multitude of compositions. For instance, thermal sprayed ceramic coatings are essential for the current and future generations of aerospace engines. Nickel-based superalloys are typically coated with thermal sprayed thermal barrier coatings (TBCs). Even the potential replacement, ceramic matrix composites (CMCs), require thermal sprayed environmental barrier coatings (EBCs) to protect them. In this context, this Ph.D. thesis is framed, working with the study of thermal sprayed coatings from powder, suspension and solution precursor. The introduction of liquid feedstocks was developed to overcome the limitations presented by powder, such as flowability with sub-micron particles, and the complexity of introducing doping elements. This thesis first presents a thorough study of the use of a novel solution precursor feedstock to produce coatings where the composition can be modified to produce functional coatings with improved properties. Taking niobium doped TiO2 as an example material, homogenously doped coatings were produced, proving the capabilities of this solution precursor route. In addition to the chemical modification, porosity was controlled through the spraying parameters, showing that microstructure can be easily tailored to the final application. In order to provide a comprehensive view accounting for the differences observed, a model detailing the evolution of the liquid feedstock as it turns into solid material during its transformation in-flight was presented. The importance of porosity, already realised in the previous stage, is the centre of the next step in the research. Conventional powder feedstock tends to produce coatings with porosity with a minimum range of tens of microns. However, this limitation is not present when suspension thermal spraying is used. To properly study this new range of pores, techniques such as image analysis are ill suited. Instead, this thesis proposes the use of more advanced techniques, such as neutron scattering techniques performed at large neutron facilities. Using yttria-stabilised zirconia, a standard TBC (where porosity has severe implications on lifetime and thermal conductivity), neutron scattering was proven as a powerful, non-destructive technique capable of accessing pores with a size of 1 nm. As a proof of concept, the evolution of porosity during heat treatment was studied and a detailed evolution study was conducted. Finally, the work in this thesis focuses on the performance of EBCs under simulated corrosive environments. As these protective coatings are expected to limit the ingress of corrosive species into the CMC substrates, porosity again plays a key role. In order to investigate this scenario, low and high porosity content EBCs were exposed to molten calcium magnesium alumino-silicates (CMAS) and superheated steam (1350 °C and 1400 °C) to assess their performance. The results show that both the low and high porosity EBCs behaved similarly, particularly during longer exposures (48 h), where inter-splat boundaries become the preferential path for access, instead of the porosity, as suggested by the literature review here presented. No evidence of failure could be detected in any of the EBCs, presenting a promising result for the development of abradable environmental barrier coatings. The work presented in this thesis represents the foundation for further research into solution precursor and suspension thermal sprayed EBCs, with both composition and porosity levels easily tailored to the end application. The new framework here discussed will ensure adequate measurement of the porosity in such coatings, accounting for sub-micron pores if using a suitable technique. Finally, these novel EBCs would require performance assessment under simulated service conditions. CMC coated samples, including high porosity abradable EBCs, would represent the natural progression of this research.